A randomized controlled trial of mindfulness to reduce stress and burnout among intern medical practitioners. (3rd April 2017) - Ireland, Michael J.; Clough, Bonnie; Gill, Kim; Langan, Fleur; O'Connor, Angela; Spencer, Lyndall
Abstract: Introduction: Stress and burnout are highly prevalent among medical doctors, and are associated with negative consequences for doctors, patients, and organizations. The purpose of the current study was to examine the effectiveness of a mindfulness training intervention in reducing stress and burnout among medical practitioners, by means of a Randomised Controlled Trial design. Methods: Participants were 44 intern doctors completing an emergency department rotation in a major Australian hospital. Participants were randomly assigned to either an active control (one hour extra break per week) or the 10-week mindfulness training intervention. Measures of stress and burnout were taken pre-, mid- and post intervention. Results: Participants undergoing the 10-week mindfulness training program reported greater improvements in stress and burnout relative to participants in the control condition. Significant reduction in stress and burnout was observed for participants in the mindfulness condition. No such reductions were observed for participants in the control condition. Conclusions: Mindfulness interventions may provide medical practitioners with skills to effectively manage stress and burnout, thereby reducing their experience of these symptoms. It is likely that doctors would benefit from the inclusion of such a training program as a part of their general medical education.